2008
DOI: 10.1103/physrevlett.101.017602
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Phase Transition inPbSc0.5Ta0.5O3as a Model Pb-Based Perovksite-Type Relaxor Ferroelectric

Abstract: We report pressure-induced structural changes in PbSc(0.5)Ta(0.5)O3 studied by single-crystal x-ray diffraction and Raman scattering. The appearance of a soft mode, a change in the volume compressibility, broadening of the diffraction peaks, and suppression of the x-ray diffuse scattering show that a phase transition occurs near pc approximately 1.9 GPa. The critical pressure is associated with a decoupling of the displacements of the B site and Pb cations in the existing polar nanoregions, leading to the supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 23 publications
5
77
2
Order By: Relevance
“…A monotonic increase of the diffuse scattering on cooling is observed in all pseudorhombohedral compositions of PMN-xPT and PZN-xPT (25,36). Other neutron and X-ray studies have demonstrated that relaxor diffuse scattering is strongly affected by external electric fields (37,38) and vanishes at high pressures (27,39). For these reasons many researchers identify the diffuse scattering with static, nanometer-scale regions of shortrange polar order known as polar nanoregions that condense from the soft TO mode on cooling from high temperatures well above T max (23,30).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…A monotonic increase of the diffuse scattering on cooling is observed in all pseudorhombohedral compositions of PMN-xPT and PZN-xPT (25,36). Other neutron and X-ray studies have demonstrated that relaxor diffuse scattering is strongly affected by external electric fields (37,38) and vanishes at high pressures (27,39). For these reasons many researchers identify the diffuse scattering with static, nanometer-scale regions of shortrange polar order known as polar nanoregions that condense from the soft TO mode on cooling from high temperatures well above T max (23,30).…”
Section: Resultsmentioning
confidence: 79%
“…To answer these questions we compared the nanoscale structures of PMN and PZT using neutron-based measurements of the elastic diffuse scattering, which is arguably the single most interesting and intensely examined property of lead-oxide relaxors to date. Strong, temperaturedependent and highly anisotropic diffuse scattering has been documented in many different lead-oxide perovskite relaxors using X-ray and neutron-scattering methods (20)(21)(22)(23)(24)(25)(26)(27). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…12,42 According to our previous highpressure studies, the critical pressure p c1 of the continuous cubic-to-rhombohedral phase transition involving a − a − a − tilting is 1.9 GPa for PST and 4.1 GPa for PSN, while the preceding pressure p is 1.2 GPa for PST and 2.5 for PSN. [28][29][30][31][32] The change in the bulk modulus K at p c1 is 44.5 GPa for PST and 15.6 GPa for PSN. The jump of K at p c1 is a combined result of the actual structural difference between the two phases as well as the material volume involved in the phase transition.…”
Section: Resultsmentioning
confidence: 99%
“…28 The Raman data up to 30 GPa show that the splitting increases with pressure [see Figs. 3 and 5(a)].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation